2013
DOI: 10.1007/s12013-013-9564-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal and Postnatal Exposure to GSM-Like Radiofrequency on Blood Chemistry and Oxidative Stress in Infant Rabbits, an Experimental Study

Abstract: We aimed to investigate the potential hazardous effects of prenatal and/or postnatal exposure to 1800 MHz GSM-like radiofrequency radiation (RFR) on the blood chemistry and lipid peroxidation levels of infant rabbits. A total of 72 New Zealand female and male white rabbits aged 1-month were used. Thirty-six female and 36 male were divided into four groups which were composed of nine infants: (i) Group 1 were the sham exposure (control), (ii) Group 2 were exposed to RFR, 15 min daily for 7 days in the prenatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Some studies indicate that 1800 MHz RFR causes oxidative stress and DNA damage in the brains and livers of pregnant rabbits and their offspring [17][18][19][20]. Another study reported that the exposure to 900 MHz RF during the prenatal period induced oxidative stress and pathologic changes in the liver tissues of rats [21].…”
Section: Oxidative Stress Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies indicate that 1800 MHz RFR causes oxidative stress and DNA damage in the brains and livers of pregnant rabbits and their offspring [17][18][19][20]. Another study reported that the exposure to 900 MHz RF during the prenatal period induced oxidative stress and pathologic changes in the liver tissues of rats [21].…”
Section: Oxidative Stress Parametersmentioning
confidence: 99%
“…Additionally, many studies have reported that 1800 MHz [17][18][19][24][25][26][27][28] and 900 MHz RFR [29,30] cause oxidative stress and DNA damage in animals. Moreover, some studies indicate that 900 MHz [6,[31][32][33][34][35][36][37][38] and 1800 MHz RFR [17,26,[39][40][41] induce oxidative stress with an increase in MDA levels.…”
Section: Oxidative Stress Parametersmentioning
confidence: 99%
“…Ozgur et al, reported that rabbits, which were exposed to EM EMF of 1800 MHz had oxydative stress and defects in serum lipid peroxydation (Ozgur et al, 2013). Czyz et al, were stated that non-thermal responses might be induced in mouse pluripotent embryonic stem cells by exposure to intermittent EMF with extremely low frequency (50 Hz) .…”
Section: Downregulated Genes That Are Taking Important Roles In Apoptmentioning
confidence: 99%
“…There's no doubt that degraded ecosystems, contaminated water, polluted indoor and outdoor air, lack of adequate sanitation, toxic hazards, disease vectors and ionizing and non-ionizing radiations are all important environmental risk factors for children therefore in developed countries there is a big interest in the maternal and neonatal health. Radiofrequency radiation (RFR), which is produced by wireless and cell phone services is one of the important environmental risk factor (2). However, in general, population vulnerable individuals such as: children, elderly people and especially pregnant women are exposed to the same degree of RFR, which is known to have an adverse health effects.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular phones are one of the man-made sources of RFR and are used more by younger generation in the last decade. Increased use of cellular phones attracts the attention of the public about adverse health effects of mobile phone radiation, especially on children and sensitive people such as pregnant women and babies (2). Increased RFR exposure can induce reactive oxygen species (ROS) to modify the cellular balance (5).…”
Section: Introductionmentioning
confidence: 99%